1996
DOI: 10.1159/000174072
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Postglomerular Capillaries in the Pathogenesis of Chronic Renal Failure

Abstract: Correlations between the relative volume of the intertubular capillaries in the renal cortex and the serum creatinine concentration in primary glomerulopathies, renal vasculopathies, and chronic interstitial nephritides are reported. In the mesangioproliferative glomerulonephritides, there are significant negative correlations between the number and area of the intertubular capillaries in the cortex and the serum creatinine concentration. In diabetic glomerulosclerosis, renal glomerular amyloidosis, decompensa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
135
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(144 citation statements)
references
References 7 publications
5
135
0
2
Order By: Relevance
“…Histological studies of human kidneys confirmed that peritubular capillary loss is correlated with interstitial fibrosis and tubular atrophy (58,59). The significance of peritubular capillary damage, with subsequent tissue hypoxia and ischemia, has been emphasized by recent findings in animal models.…”
Section: Loss Of Peritubular Capillaries In Chronic Renal Diseasementioning
confidence: 89%
“…Histological studies of human kidneys confirmed that peritubular capillary loss is correlated with interstitial fibrosis and tubular atrophy (58,59). The significance of peritubular capillary damage, with subsequent tissue hypoxia and ischemia, has been emphasized by recent findings in animal models.…”
Section: Loss Of Peritubular Capillaries In Chronic Renal Diseasementioning
confidence: 89%
“…32 Furthermore, the experimental adminis- . Control cells and HIF2a clones (#3 and #7) were seeded at 1.0 Â 10 5 per six-well plate and cultured in either normoxia or hypoxia for up to 72 h. There was no difference in growth among these clones in the monolayer culture system.…”
Section: Hif-mediated Angiogenesis In the Kidneymentioning
confidence: 99%
“…Given the observations that the degree of tubulointerstitial injury correlates with renal insufficiency 54 and that the damage in this compartment is correlated with loss of peritubular capillaries, 32 angiogenesis through activation of HIF is a promising therapeutic target against progressive, hypoxic renal diseases. In this sense, modalities that activate HIF, including methods to inhibit prolyl-hydroxylase activities, 55,56 should be eagerly pursued.…”
Section: Hif-mediated Angiogenesis In the Kidneymentioning
confidence: 99%
“…These glomerular changes are followed by tubulointerstitial fibrosis, which progresses into eventual renal failure. [21][22][23] Cytokines such as IL-1, tumor necrosis factor-a (TNFa) and substances derived from platelets have a role in augmenting neutrophil-mediated glomerular damages. 24 Through the release of inflammatory cytokines, macrophages may also stimulate mesangial cells to proliferate and synthesize ECM proteins.…”
Section: Discussionmentioning
confidence: 99%